Measurement of the cross section for isolated-photon plus jet production in pp collisions at √s = 13 TeV using the ATLAS detector - Alconada Verzini, María Josefina (2018)
The dynamics of isolated-photon production in association with a jet in proton–proton collisions at a centre-of-mass energy of 13 TeV are studied with the ATLAS detector at the LHC using a dataset with an integrated luminosity of 3.2 fb−1. Photons are required to have transverse energies above 125 GeV. Jets are identified using the anti-kt algorithm with radius parameter R = 0.4 and required to have transverse momenta above 100 GeV. Measurements of isolated-photon plus jet cross sections are presented as functions of the leading-photon transverse energy, the leading-jet transverse momentum, the azimuthal angular separation between the photon and the jet, the photon–jet invariant mass and the scattering angle in the photon–jet centre-of-mass system. Tree-level plus parton-shower predictions from Sherpa and PYTHIA as well as next-to-leading-order QCD predictions from JETPHOX and SHERPA are compared to the measurements.